Hands-on Learning for Freshman Engineering Students - Julie Arnold; Robert Kackley; Stephen Fortune (Issues in Science and Technology Librarianship)
Formal library orientation sessions for freshman engineering students have been offered for more than seven years by librarians in the Engineering and Physical Sciences Library (EPSL), University of Maryland. Approximately 800 students per year attend these sessions. The sessions are conducted in the library and are required by all students enrolled in ENES 100 (Introduction to Engineering Design). In the spring of 2001 the orientation sessions were reformatted based on comments contained in short surveys completed by students at the end of each session. The format was changed from completely lecture-based to a more interactive session entitled "EPSL Expedition." In addition, during this same semester, librarians volunteered to rewrite and update the chapter on "Library Research Skills" for the course textbook, Introduction to Engineering Design by James W. Dally. This paper will attempt to answer the following question: Do freshman engineering students learn and retain more information through an "interactive" orientation session than they do from a "lecture" based session?